BS EN 17550. Animal feeding stuffs: Methods of sampling and analysis. Determination of carotenoids in animal compound feed and premixtures by high performance liquid chromatography. UV detection (HPLC-UV). (17th September 2020) - British Standards Institution,
No abstract available